The appleization of finance: Charting incumbent finance's embrace of FinTech - Reijer Hendrikse; David Bassens; Michiel Van Meeteren (Finance and Society, 2018)
The rise of financial technology (FinTech) engenders novel business models through integrating financial services and information and communication technologies (ICT). Digital currencies and payments, data mining, and other FinTech applications threaten to radically overhaul the financial sector. This article argues that, while we are becoming aware of how technology giants such as Apple Inc. are making inroads into financial services, we need to become more sensitive to how financial incumbents mimick ICT firms while aiming to neutralize the FinTech challenge. Practices from Silicon Valley are spilling over into "traditional" finance through a process we dub Appleization . We illustrate how incumbents aim to remain indispensable amidst rapid digitization. Mimicking tech strategies, financial incumbents resort to transforming legacy ICT systems into integrated platforms, cultivating entrepreneurial ecosystems where startups are 'free' to compete whilst effectively being locked into the incumbent's orbit. We illustrate this by comparing Apple's business features (locking-in developers, customers and state into a hybrid business model based on a synergy between hardware, software and data-driven platform components) with emerging practices in the financial industry. Our analogy suggests that the Appleization of finance might radically transform, yet not undercut the oligopolistic position of financial incumbents.
Keywords: 300; FinTech; financial innovation; platform capitalism; entrepreneurial ecosystem